Barriers to gene therapy, understanding the concerns people with haemophilia have: an exigency sub-study - Fletcher, Simon; Jenner, Kathryn; Holland, Michael; Khair, Kate (Orphanet journal of rare diseases, 2024)
Background Gene therapy has the potential to offer people with haemophilia (PwH) a life free from bleeding and the burden posed by current treatment regimens. To date, gene therapy has only been available in clinical trial settings, to PwH without pre-existing or historical factor inhibitors, significant concomitant liver damage or pre-existing neutralising antibodies to the adeno-associated viruses used to deliver the therapy. Thus, most PwH treated at centres not currently involved in gene therapy trials, either as a referral/follow-up centre or as a dosing centre, have been unable to access the therapy. This Exigency sub-study aims to gain a greater understanding of the opinions of PwH in the United Kingdom who have not had access to gene therapy: asking what they understand, what concerns they have, and whether they perceive any barriers preventing their access to gene therapy. Results Twenty-three PwH were approached; 14 consented, and one withdrew prior to interview. The mean age of the participants was 35.7 years (range 25–74 years). Eleven had haemophilia A and two haemophilia B. Two were treated with standard half-life factor products, five with extended half-life products, five with a FVIII mimetic and one with a clinical trial product. One family member (a participant's partner) was also interviewed. The participants identified four barriers to gene therapy: concerns about the process of gene therapy (Expectations), uncertainty about the results (outcomes), (Access) to treatment, and a lack of understanding about gene therapy (education). Conclusions This Exigency study subgroup sees gene therapy as a positive treatment development that promises an improved quality of life. For this participant group, four issues impact their decision to undergo gene therapy. If the promise of gene therapy is to be realised, these barriers need to be acknowledged and addressed by healthcare professionals, patient organisations, and gene therapy providers.